Polyhydroxyalkanoates synthesis using acidogenic fermentative effluents - Banu, J. Rajesh; Ginni, G.; Kavitha, S.; Kannah, R. Yukesh; Kumar, Vinod; Kumar, S. Adish; Gunasekaran, M.; Tyagi, Vinay Kumar; Kumar, Gopalakrishnan (Elsevier, 2021)
Polyhydroxyalkanoates (PHA) are natural polyesters synthesized by microbes which consume excess amount of carbon and less amount of nutrients. It is biodegradable in nature, and it synthesized from renewable resources. It is considered as a future polymer, which act as an attractive replacement to petrochemical based polymers. The main hindrance to the commercial application of PHA is the high manufacturing cost. This article provides an overview of different cost-effective substrates, their characteristics and composition, major strains involved in economical production of PHA and biosynthetic pathways leading to accumulation of PHA. This review also covers the operational parameters, various fermentative modes including batch, fed-batch, repeated fed-batch and continuous fed-batch systems, along with advanced feeding strategies such as single pulse carbon feeding, feed forward control, intermittent carbon feeding, feast famine conditions to observe their effects for improving PHA synthesis and associated challenges. In addition, it also presents the economic analysis and future perspectives for the commercialization of PHA production process thereby making the process sustainable and lucrative with the possibility of commercial biomanufacturing.
Keywords: PHA; Biosynthetic pathways; Fermentative modes